2010
DOI: 10.1161/circoutcomes.109.884361
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in Duration of Prehospital Delay in Patients With Acute Myocardial Infarction

Abstract: Background-Coronary heart disease is the leading cause of morbidity and mortality in American men and women.Although there have been dramatic changes in the management of patients hospitalized with acute myocardial infarction (AMI) over the past several decades, a considerable proportion of patients with AMI continue to delay seeking medical care in a timely manner. This review provides an overview of the published literature that has examined age and sex differences in extent of prehospital delay in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
160
8
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(202 citation statements)
references
References 61 publications
15
160
8
19
Order By: Relevance
“…In addition, international guidelines recommend that reperfusion therapy should be performed within 90 min after the onset of symptoms [23]. A recent systematic review has shown the reliability of reporting pre-hospital delay and the effect of patient features on it [24]. On the other hand, studies comparing yearly trends of reported pre-hospital delay have interestingly remarked that average delay times have remained essentially unchanged during the past two decades [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, international guidelines recommend that reperfusion therapy should be performed within 90 min after the onset of symptoms [23]. A recent systematic review has shown the reliability of reporting pre-hospital delay and the effect of patient features on it [24]. On the other hand, studies comparing yearly trends of reported pre-hospital delay have interestingly remarked that average delay times have remained essentially unchanged during the past two decades [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of studies that have examined extent of prehospital delay among patients presenting with AMI in the United States have found median delays of ≈2 to 3 hours7, 8, 17, 20, 21, 22, 23 with most of these studies showing higher delay times in elderly than in younger patients,8, 24 few studies have examined the magnitude of, and factors associated with, prolonged delay in seeking medical care after onset of acute coronary symptoms in elderly patients presenting with AMI 9. Furthermore, we were unable to find any published studies that examined the extent of prehospital delay within different age strata of elderly patients hospitalized with an AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we were unable to find any published studies that examined the extent of prehospital delay within different age strata of elderly patients hospitalized with an AMI. Many studies have, however, included varying proportions of elderly patients in their study population and observed median prehospital delays ranging from 2.2 to 2.8 hours in these patients 7, 8, 9, 25…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations